The uniqueome: a mappability resource for short-tag sequencing - Koehler, Ryan (Oxford University Press, 2011)
Summary: Quantification applications of short-tag sequencing data (such as CNVseq and RNAseq) depend on knowing the uniqueness of specific genomic regions at a given threshold of error. Here, we present the ‘uniqueome’, a genomic resource for understanding the uniquely mappable proportion of genomic sequences. Pre-computed data are available for human, mouse, fly and worm genomes in both color-space and nucletotide-space, and we demonstrate the utility of this resource as applied to the quantification of RNAseq data. Availability: Files, scripts and supplementary data are available from http://grimmond.imb.uq.edu.au/uniqueome/; the ISAS uniqueome aligner is freely available from http://www.imagenix.com/. Contact: n.cloonan@uq.edu.au Supplementary information: Supplementary data are available at Bioinformatics online.